Smart hybrid renewable microgeneration system for residential applications. (2017) - Lee, Euy Joon; Entchev, Evgueniy; Yang, Libing; Ghorab, Mohamed; Kang, Eun Chul
Microgeneration systems generate power and heat at the point of use by utilising a variety of conventional and renewable technologies. They demonstrate a comparable electric efficiency to the conventional power generation stations, good environmental performance and ability to serve as a source for both primary and back-up power. Assembled in microgrids or in 'virtual power plant' they can serve multiple buildings and be active participants in load management efforts both on site and on the grid. The study investigates the performance of a hybrid renewable ground source heat pump (GSHP)/photovoltaic thermal (PVT) microgeneration system serving multiple residential and small office buildings in Ottawa, Canada and Incheon, South Korea. The analysis shows that the energy performance of the GSHP/PVT system results in considerable overall energy savings in comparison to conventional and single GSHP system due to the higher renewable component. The energy analysis results indicate that the extra capital investment incurred to the GSHP-PVT system is possible to be returned within its lifespan, especially with the current trend of continuous equipment and installation price reductions. Further reducing of buildings' dependence from the electricity grid could also be achieved within the 'smart energy networks' concept and with utilities various load shaving and load levelling strategies.